Does intergenerational mobility shape psychological distress? Sorokin revisited - Houle, Jason N. (2011)
Drawing from Sorokin's hypothesis that socially mobile individuals are at greater risk of experiencing psychological distress than their non-mobile counterparts, we investigate whether intergenerational occupational mobility influences psychological distress, as measured by the Center for Epidemiologic Studies Depression (CES-D) scale. Using data for men from the Wisconsin Longitudinal Study (WLS) and Sobel's Diagonal Mobility Models, we find little evidence for Sorokin's hypothesis; mobile individuals are no more likely to be psychologically distressed than their non-mobile counterparts. In fact, one group of mobile men – those who left their farming origins – are actually less distressed than the sons who remain as farmers and non-mobile men in higher-ranked social classes. We speculate that this reflects the fact that farming became very arduous during the late 20th century and these mobile sons of farmers appreciate their improved life chances. Our findings suggest that the association between mobility and psychological distress varies across specific class backgrounds and is contingent upon the broader social and economic context.